Cuphea hookeriana: Phytochemical Profile and the Cosmeceutical and Dermatological Properties of Its Active Fraction from the Whole Plant - Xing Wu; Meng-Fei Wanyan; Bao-Bao Shi; Rong Huang; Hui-Xiang Yang; Xian Wang; Ji-Kai Liu (Molecules)
Natural products and botanicals continue to play a very important role in the development of cosmetics worldwide. The chemical constituents of a fine active fraction of the whole plant extract of Cuphea hookeriana Walp., and the tyrosinase and matrix metalloproteinase-1 (MMP-1) inhibitory and antioxidant activities of this fraction were investigated. The fine active fraction was mainly composed of seven natural compounds. The fine active fraction demonstrated substantial in vitro antioxidant potential using the ABTS assay (IC50 1.66 μg/mL). It inhibited the two target enzymes (tyrosinase and MMP-1) engaged in skin whitening and aging with comparable IC50 values to the reference drugs. Acute toxicity experiments showed that mice gavage orally with the fine active fraction had no significant animal toxicity at a dose of 2000 mg/kg, and the maximum tolerated dose (MTD) in mice was greater than 2000 mg/kg. In a model where ultraviolet light promotes the increase in melanin secretion in guinea pig skin tissues, both α-arbutin and the fine active fraction can reduce melanogenesis, and the effect of the fine active fraction is better than that of α-arbutin.